The High Prevalence of Thermolabile 5-10 Methylenetetrahydrofolate Reductase (MTHFR) in Italians Is not Associated to an Increased Risk for Coronary Artery Disease (CAD) - Abbate, Rosanna; Sardi, Iacopo; Pepe, Guglielmina; Marcucci, Rossella; Brunelli, Tamara; Prisco, Domenico; Fatini, Cinzia; Capanni, Monia; Simonetti, Ignazio; Gensini, Gian Franco (Thrombosis and Haemostasis, 1998)
Mild hyperhomocysteinemia was found to be related to venous thrombosis, cerebrovascular and coronary artery disease (CAD). Some recent studies suggested that a mutation in the gene encoding for 5-10 methylenetetrahydrofolate reductase (MTHFR), due to a transition C→ at nucleotide 677, is a genetic risk factor for vascular disease. However, several further studies could not confirm this association.We investigated 84 patients with CAD who underwent percutaneous transluminal coronary angioplasty (PTCA) and 106 healthy subjects.The prevalence of the mutated homozygous genotype was much higher than in other Italian populations, Europeans or other major human groups, but no excess of the Val/Val homozygotes was found in patients (28.5%) with respect to healthy subjects (30.2%). Mutated homozygous MTHFR genotype (+/+) was not found to be related to the clinical manifestations of CAD, to the prevalence of the common risk factors and to the rate of restenosis.In conclusion, thermolabile MTHFR does not appear to be associated “per se” with the risk for CAD or for restenosis after PTCA. The high frequency of the +/+ genotype in our Italian population (from Tuscany) confirms a wide macroheterogeneity and suggests a microheterogeneity in the genotype frequencies of the different ethnic populations.Preliminary data of this paper were selected for an Oral Communication at the XVIth ISTH Congress.